Lithium ion battery electrolyte and lithium ion battery thereof
By using Compounds A and Compound B in the lithium-ion battery electrolyte, the performance degradation of lithium-ion batteries under high and low temperature conditions is solved, and better cycling performance and low temperature performance are achieved.
Patent Information
- Application Number
- CN202411500496.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-10-25
AI Technical Summary
Existing lithium-ion batteries have deteriorated performance at high temperatures, especially at low temperature conditions, resulting in poor circulation and low temperature performance.
A lithium-ion battery electrolyte is used, including lithium salts, non-aqueous organic solvents and additives. The non-aqueous organic solvents contain carbonate compounds and the additives contain compounds A and B. Compound A has a low oxidation potential, can form an optimized interface layer on the electrode surface, improving lithium ion transport efficiency; Compound B has the Lewis base characteristics, can complex with the acidic substances produced by Compound A, and inhibit the decomposition of the SEI film.
Through the synergistic action of compound A and compound B, the interface side reactions of lithium-ion batteries during circulation and storage are reduced, effectively inhibiting the decomposition of the SEI interface, and improving the circulation and low-temperature performance of lithium-ion batteries.
Smart Images

Figure CN119400954A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium ion batteries, and in particular relates to a lithium ion battery electrolyte and a lithium ion battery thereof. Background Art
[0002] Lithium-ion batteries have been widely used in many fields due to their high operating voltage, high energy density, long cycle life and relatively environmentally friendly characteristics. Especially in the field of 3C (computer, communication and consumer electronics) products, lithium-ion batteries have almost become a standard configuration for portable electronic devices. With the advancement of technology and the growing demand of consumers for thinner and lighter designs, lithium-ion battery technology is also constantly evolving to adapt to these new demands.
[0003] The performance of lithium-ion batteries will be affected by the oxidative decomposition of the electrolyte, especially under the conditions of cyclic use and high-temperature storage, the dissolution of metal ions will further lead to a significant decrease in battery performance. With the growth of market demand for lithium-ion batteries, the requirements for their comprehensive performance are also increasing. In order to solve these problems and improve the overall performance of the battery, the use of additives has become an effective means. There are many types of additives, which can be divided into: film-forming additives, overcharge protection additives, conductive additives, flame retardant additives, electrolyte stabilizers, etc. according to the different roles played by the additives in the electrolyte. Regardless of the type of additive, it accounts for a small proportion in the electrolyte, but it has been widely researched and developed due to its obvious functions.
[0004] In order to improve the high temperature performance of lithium-ion batteries, carbonate compounds are generally selected as the main component of non-aqueous organic solvents. However, carbonate compounds have a high melting point, and the conductivity of the electrolyte drops very quickly at low temperatures, and the battery impedance increases rapidly, making it difficult to meet the low temperature discharge performance of the battery. In terms of additives, in order to further improve the high temperature performance, auxiliary agents such as vinylene carbonate and vinyl ethylene carbonate are generally used, but this type of auxiliary agent will also cause a large battery impedance, especially at low temperatures, the battery impedance increases significantly, resulting in a decrease in the low temperature performance of the battery.
[0005] Therefore, there is an urgent need for a lithium ion battery electrolyte and a lithium ion battery thereof to solve the deficiencies of the prior art problems. Summary of the invention
[0006] In view of the above problems, an object of the present invention is to provide a lithium ion battery electrolyte and a lithium ion battery thereof, wherein the lithium ion battery electrolyte can improve the cycle performance and low temperature performance of the lithium ion battery.
[0007] To achieve the above objectives, the present invention provides a lithium ion battery electrolyte in a first aspect, comprising a lithium salt, a non-aqueous organic solvent and an additive, wherein the non-aqueous organic solvent comprises a carbonate compound, and the additive comprises a compound A represented by structural formula I and a compound B represented by structural formula II;
[0008]
[0009] Wherein R1 is selected from halogen, R2 to R4 are each independently selected from halogen, alkyl, alkenyl, alkynyl or silane, m is selected from 0 or 1, and X is selected from carbon, sulfur or phosphorus.
[0010] Compared with the prior art, the lithium ion electrolyte of the present invention includes lithium salt, non-aqueous organic solvent and additive, the non-aqueous organic solvent includes carbonate compounds, the additive includes compound A and compound B containing special structures, compound A has a relatively low oxidation potential, can be oxidized before the solvent on the electrode surface, and form a thinner interface layer, the interface layer has a better lithium ion transmission efficiency, is not easy to shrink holes at low temperatures, can maintain the lithium ion transmission channel at low temperatures, and improve the low temperature performance of lithium ion batteries, but the FS bond in the compound A has low bond energy and is easy to break, and then defluorinates with α-H on the carbonate compound, resulting in an increase in the acid value of the electrolyte, so compound A is prone to produce acidic substances, which damage the SEI film and cause the battery's cycle performance to deteriorate. The compound B of the present application can not only polymerize at the negative electrode to form a high-toughness SEI, but also exhibits Lewis base characteristics, can complex the acidic substances produced by compound A, and inhibit the damage of the acidic substances to the electrode electrolyte interface, and the battery's cycle performance is guaranteed. In summary, the present invention utilizes the synergistic effect of compound A and compound B to reduce the interfacial side reactions during battery cycling and storage, effectively inhibit the decomposition of the SEI interface, and thus improve the cycling performance and low-temperature performance of lithium-ion batteries.
[0011] Further, R2 to R4 of the present invention are independently selected from halogen, C1-C6 alkyl, C2-C6 alkenyl, C2-C6 alkynyl or C1-C6 silyl, and R2 to R4 groups are the same. Specifically, halogen can be fluorine (F), chlorine (Cl), bromine (Br), iodine (I). C1-C6 alkyl refers to a straight chain or branched saturated hydrocarbon group containing 1 to 6 carbon atoms, and these alkyl groups can be straight chain (normal) or with branches (isomerism), such as but not limited to methyl, ethyl, n-propyl, isopropyl, n-butyl, tert-butyl, etc. C2-C6 alkenyl refers to an unsaturated hydrocarbon group containing 2 to 6 carbon atoms and at least one double bond. These alkenyl groups can be straight chain or with branches, and the double bonds can be in different positions; such as C2-C6 alkenyl can be but not limited to vinyl, propenyl, isopropenyl, butenyl, pentenyl, hexenyl. C2-C6 alkynyl refers to an unsaturated hydrocarbon group containing 2 to 6 carbon atoms and at least one triple bond, and these alkynyl groups can be straight chain or branched, such as C2-C6 alkynyl can be but not limited to ethynyl, propynyl, butynyl, pentynyl, hexynyl. C1-C6 silyl refers to an organic group containing 1 to 6 carbon atoms and directly connected to a silicon atom, and these groups can be in the form of straight chain or branched, such as C1-C6 silyl can be but not limited to -Si(CH3)3, -Si(CH3)2(C2H5).
[0012] Furthermore, the compound A of the present invention is at least one selected from the group consisting of compounds A1 to A3:
[0013]
[0014] Furthermore, the compound B of the present invention is selected from at least one of compounds B1 to B4:
[0015]
[0016] Further, the mass percentage of compound A in the lithium ion battery electrolyte of the present invention is 0.1-10.0%; specifically, the mass percentage of compound A in the non-aqueous electrolyte may be, but is not limited to, 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 7%, 8%, 9%, 10%. Preferably, the mass percentage of compound A in the lithium ion battery electrolyte is 0.1-2%.
[0017] Further, the mass percentage of compound B in the lithium ion battery electrolyte of the present invention is 0.1-10.0%. Specifically, the mass percentage of compound B in the non-aqueous electrolyte may be, but is not limited to, 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 6%, 7%, 8%, 9%, 10%. Preferably, the mass percentage of compound B in the lithium ion battery electrolyte is 0.1-2%.
[0018] Further, the lithium salt of the present invention includes at least one of lithium hexafluorophosphate (LiPF6), lithium perchlorate (LiClO4), lithium tetrafluoroborate (LiBF4), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethylsulfonyl)imide (LiTFSI), lithium methanesulfonate, lithium trifluoromethylsulfonate, lithium fluorosulfonate, lithium bis(oxalate)borate, lithium difluorooxalate borate, lithium difluorophosphate, lithium difluorobis(oxalate)phosphate, lithium diphosphate and lithium lower aliphatic carboxylate. Specifically, the mass percentage of lithium salt in the lithium ion battery electrolyte is 5 to 30%, such as the content of lithium salt can be but not limited to 5%, 10%, 15%, 20%, 25%, 30%; preferably, the mass percentage of lithium salt in the lithium ion battery electrolyte is 5 to 18%.
[0019] Further, the carbonate compounds of the present invention include cyclic carbonates and chain carbonates. Specifically, the cyclic carbonates may be, but are not limited to, ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), pentylene carbonate, vinylene carbonate (VC) or their derivatives; chain carbonates include, but are not limited to, dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), and propylene carbonate.
[0020] Furthermore, the non-aqueous organic solvent of the present invention further comprises at least one of a carboxylate compound and an ether compound. Both carboxylate compounds and ether compounds are polar solvents that can dissolve lithium salts well to form a stable lithium ion battery electrolyte. More specifically, carboxylate compounds can provide a higher dielectric constant, and ether compounds can provide better low temperature performance.
[0021] Furthermore, the carboxylic acid esters of the present invention include at least one of cyclic carboxylic acid esters and chain carboxylic acid esters. The cyclic carboxylic acid esters may specifically include but are not limited to at least one of γ-butyrolactone (GBL), γ-valerolactone (GVL), and δ-valerolactone (DVL); the chain carboxylic acid esters include but are not limited to methyl acetate (MAC), ethyl acetate (EA), propyl acetate (PA), butyl acetate (BA), propyl propionate (PP), and butyl propionate (BP).
[0022] Furthermore, the ether compounds of the present invention include cyclic ethers or chain ethers. The cyclic ethers may specifically include but are not limited to at least one of 1,3-dioxolane (DOL), 1,4-dioxolane (DX), crown ethers, tetrahydrofuran (THF), 2-methyltetrahydrofuran (2-CH3-THF), and 2-trifluoromethyltetrahydrofuran (2-CF3-THF); the chain ethers may specifically include but are not limited to dimethoxymethane, diethoxymethane, ethoxymethoxymethane, ethylene glycol di-n-propyl ether, ethylene glycol di-n-butyl ether, and diethylene glycol dimethyl ether.
[0023] Furthermore, the lithium ion battery electrolyte of the present invention further comprises an auxiliary agent, and the auxiliary agent is selected from vinylene carbonate (VC), vinylene carbonate (VEC), fluoroethylene carbonate (FEC), vinyl sulfite (ES), 1,3-propane sultone (PS), 1,3-propylene sultone (PES), 1,4-butane sultone (BS), vinyl sulfate (DTD), succinic anhydride (SA), maleic anhydride (MA), 2-methylmaleic anhydride (MMA), methyl carbonate-2-propynyl ester, tetravinylsilane, triallyl At least one of isocyanurate, hexamethylene diisocyanate, o-phenanthroline, p-phenylene diisocyanate, 2,4-toluene diisocyanate, N-phenyl bis(trifluoromethanesulfonyl)imide, vinyl disulfate, phenyl methanesulfonate, vinyl disulfate, bis-spirosulfate, hydroquinone difluorosulfonate, triallyl phosphate, tripropargyl phosphate, 2,4-butane sultone, methacrylate isocyanoethyl, methane disulfonic acid methylene ester, tri(trimethylsilyl) borate, tri(trimethylsilyl) phosphate, tri(vinyldimethylsilyl) phosphate. Specifically, the mass percentage of the auxiliary agent of the present invention in the lithium ion battery electrolyte is 0.1-5%, such as the auxiliary agent content can be but not limited to 0.1%, 0.5%, 1%, 1.6%, 1.9%, 2.6%, 3.2%, 3.8%, 4.3%, 4.8%, 5%. Preferably, the mass percentage of the auxiliary agent in the lithium ion battery electrolyte is 0.1-2%.
[0024] Correspondingly, the second aspect of the present invention also provides a lithium ion battery, comprising a positive electrode, a negative electrode, and the above-mentioned lithium ion battery electrolyte. The lithium ion battery has good cycle performance and low temperature performance.
[0025] Furthermore, the active materials of the positive electrode of the present invention include lithium-containing phosphates with an olivine structure, lithium transition metal oxides and their respective modified compounds. Specifically, the lithium-containing phosphates with an olivine structure include, but are not limited to, at least one of lithium iron phosphate (such as LiFePO4), a composite material of lithium iron phosphate and carbon, lithium manganese phosphate (such as LiMnPO4), a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate, and a composite material of lithium iron manganese phosphate and carbon. Lithium transition metal oxides include, but are not limited to, lithium cobalt oxide (such as LiCoO2), lithium nickel oxide (such as LiNiO2), lithium manganese oxide (such as LiMnO2, LiMn2O4), lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide (structure such as LiNi x Co y Mn 1-x-y M z O2, wherein 0.6≤x<0.9, x+y<1, 0≤z<0.08, M is at least one of Al, Mg, Zr and Ti). Preferably, the active material of the positive electrode of the present invention is LiNi 0.8 Co 0.1 Mn 0.1 Zr 0.03 O2.
[0026] Furthermore, the active material of the negative electrode of the present invention includes at least one of a carbon-based negative electrode, a silicon-based negative electrode, a tin-based negative electrode, and a lithium negative electrode. The carbon-based negative electrode may include graphite, hard carbon, soft carbon, graphene, mesophase carbon microspheres, etc.; the silicon-based negative electrode may include silicon materials, silicon oxides, silicon-carbon composite materials, and silicon alloy materials, etc.; the tin-based negative electrode may include tin, tin carbon, tin oxygen, and tin metal compounds; the lithium negative electrode may include metallic lithium or a lithium alloy. The lithium alloy may specifically be at least one of a lithium silicon alloy, a lithium sodium alloy, a lithium potassium alloy, a lithium aluminum alloy, a lithium tin alloy, and a lithium indium alloy. DETAILED DESCRIPTION
[0027] In order to further illustrate the purpose, technical scheme and beneficial effects of the present invention, the present invention will be further described below in conjunction with specific examples. It should be noted that, if specific conditions are not specified in the examples and comparative examples, they can be carried out according to conventional conditions or conditions recommended by the manufacturer, and if the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be obtained commercially.
[0028] Example 1
[0029] This embodiment provides a method for preparing a lithium ion battery, the steps comprising:
[0030] (1) The ternary material LiNi 0.8 Co 0.1 Mn 0.1 Zr 0.03O2, conductive agent SuperP, adhesive PVDF and carbon nanotubes (CNT) are mixed evenly in a mass ratio of 96.5:1.5:1:1 to form a lithium-ion battery positive electrode slurry with a certain viscosity, which is coated on the aluminum foil for current collector. The coating amount is 324g / m 2 , dried at 85°C and then cold pressed; then trimmed, cut into pieces, and slit, and then dried at 85°C for 4 hours under vacuum conditions, and the tabs were welded to make positive electrode sheets that meet the requirements;
[0031] (2) artificial graphite and silicon are mixed in a mass ratio of 90:10, and then mixed with a conductive agent SuperP, a thickener CMC, and an adhesive SBR (styrene-butadiene rubber latex) in a mass ratio of 95:1.5:1.0:2.5 to make a slurry, which is mixed evenly, and the mixed slurry is applied on both sides of a copper foil, and then dried and rolled to obtain a negative electrode sheet, thereby making a negative electrode sheet that meets the requirements;
[0032] (3) In a glove box filled with nitrogen (O2 <1ppm, H2O <1ppm), ethylene carbonate (EC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), propyl propionate (PP), and dimethoxymethane (DMM) are mixed in a mass ratio of 3:3:4:2:2 to obtain a mixed solvent as a non-aqueous organic solvent, and then additives and auxiliary agents are added to obtain a mixed solution. The mixed solution is sealed and packaged and placed in a quick freezer (-4°C) for 2 hours, then taken out, and in a glove box filled with nitrogen (O2 <1ppm, H2O <1ppm), lithium hexafluorophosphate is slowly added to the mixed solution, and after mixing evenly, a lithium ion battery electrolyte is prepared;
[0033] (4) The positive electrode sheet, negative electrode sheet and separator are laminated to form a lithium-ion battery with a thickness of 4.7 mm, a width of 55 mm and a length of 60 mm. The battery is vacuum-baked at 75°C for 10 h and the lithium-ion battery electrolyte is injected. After standing for 24 h, the battery is charged to 4.4 V at a constant current of 0.1 C (180 mA), and then charged at a constant voltage of 4.4 V until the current drops to 0.05 C (90 mA); then discharged to 3.0 V at 0.2 C (180 mA), and the charge and discharge are repeated twice. Finally, the battery is charged to 3.8 V at 0.2 C (180 mA) to obtain a lithium-ion battery.
[0034] The formulas of the lithium ion battery electrolytes of Examples 1 to 16 and Comparative Examples 1 to 6 are shown in Table 1, wherein the preparation processes of the lithium ion battery electrolytes, positive electrode sheets, negative electrode sheets, and lithium ion batteries of Examples 2 to 16 and Comparative Examples 1 to 6 are the same as those of Example 1.
[0035] Table 1 Formulas of lithium ion battery electrolytes of Examples and Comparative Examples
[0036]
[0037] Lithium-ion battery electrolyte acidity test:
[0038] Weigh 20 g of the lithium ion battery electrolyte prepared in the above Examples 1 to 9 and Comparative Example 5, place it in a conical flask, weigh it and record it as mass M, add 1 to 2 drops of neutral red methylene blue mixed indicator, use triethylamine ultra-dry acetonitrile solution with a concentration of C to titrate, record the titration volume V of the standard solution, and calculate the electrolyte acidity according to the following formula: electrolyte acidity (ppm) = 20.006 × 1000 × V × C / M;
[0039] The remaining lithium-ion battery electrolyte was placed in a clean and dry aluminum-plastic bottle, sealed and placed in a 60°C oven for three days, then the lithium-ion battery electrolyte was taken out and the acidity of the lithium-ion battery electrolyte was measured again according to the above method. The test results are shown in Table 2.
[0040] Table 2 Acidity test results of lithium-ion battery electrolyte
[0041] Group Acidity before storage / ppm Acidity / ppm after 3 days storage at 60℃ Example 1 23.01 46.85 Example 2 25.32 46.35 Example 3 25.87 48.32 Example 4 25.85 45.37 Example 5 25.47 48.42 Example 6 24.39 47.18 Example 7 23.05 45.71 Example 8 23.61 48.60 Example 9 23.01 48.87 Comparative Example 5 24.68 189.73
[0042] From the test results in Table 2, it can be seen that if only compound A is present, the acid value of the electrolyte increases significantly. This is because the FS bond in compound A has low bond energy and is easily broken, and then undergoes a defluorination reaction with the α-H on the carbonate compound, resulting in an increase in the acid value of the electrolyte. Compound B can complex the acidic substances produced by compound A, thereby inhibiting the increase in the acid value of the electrolyte.
[0043] The lithium ion batteries prepared in Examples 1 to 16 and Comparative Examples 1 to 6 were subjected to high temperature storage performance test, high temperature cycle performance test, room temperature cycle performance test, and low temperature performance test under the following conditions. The results are shown in Table 3.
[0044] High temperature storage performance test :
[0045] At room temperature (25°C), the lithium-ion battery was charged and discharged at 0.5C / 0.5C (the battery discharge capacity was recorded as C0), with an upper limit voltage of 4.4V, and then the battery was charged to 4.4V under 0.5C constant current and constant voltage conditions, and the battery thickness was measured (the thickness was recorded as D0); the battery was placed in a 60°C oven for 30 days, taken out and the battery thickness was measured (the thickness was recorded as D1); the battery was placed in a 25°C environment and discharged at 0.5C (the discharge capacity was recorded as C1); the lithium-ion battery was continued to be charged and discharged at room temperature (25°C) at 0.5C / 0.5C (the battery discharge capacity was recorded as C2), with an upper limit voltage of 4.4V, and the capacity retention rate, capacity recovery rate and thickness expansion rate were calculated.
[0046] Capacity retention rate = (C1 / C0)*100%
[0047] Capacity recovery rate = (C2 / C0)*100%
[0048] Thickness expansion rate = (D1 / D0)*100%
[0049] Normal temperature cycle performance test :
[0050] At room temperature (25°C), the lithium-ion battery is charged and discharged at 1.0C / 1.0C once (the battery discharge capacity is C0) with an upper voltage of 4.4V, and then charged and discharged at 1.0C / 1.0C for 500 cycles at room temperature (the battery discharge capacity is C1), and the capacity retention rate is calculated.
[0051] Capacity retention rate = (C1 / C0)*100%
[0052] High temperature cycle performance test :
[0053] Under high temperature (45°C) conditions, the lithium-ion battery is charged and discharged at 1.0C / 1.0C once (the battery discharge capacity is C0) with an upper voltage of 4.4V, and then charged and discharged at 1.0C / 1.0C for 400 cycles at room temperature (the battery discharge capacity is C1), and the capacity retention rate is calculated.
[0054] Capacity retention rate = (C1 / C0)*100%
[0055] Low temperature performance test :
[0056] At room temperature (25°C), the lithium-ion battery is charged and discharged at 0.5C / 0.5 (battery cut-off voltage is 3.0V, discharge capacity is C0), and the upper limit voltage is 4.4V (cut-off current 0.05C). Then the battery is fully charged to 4.4V (cut-off current 0.05C) at 0.5C at room temperature (25°C), and then the battery is transferred to -20°C and left for 4 hours, and discharged to 3.0V at 0.5C, and the discharge capacity is C1. The capacity retention rate is calculated.
[0057] Capacity retention rate = (C1 / C0)*100%
[0058] Table 3 Lithium-ion battery performance test results
[0059]
[0060]
[0061] As can be seen from Table 3, compared with Comparative Example 1, Examples 1 to 16 include Compound A and Compound B in their non-aqueous electrolytes, and the lithium-ion batteries not only have good high-temperature storage performance and high-temperature cycle performance, but also have good low-temperature performance at -20°C. This is because Compound A has a relatively low oxidation potential, can be oxidized before the solvent on the electrode surface, and form a thinner interface layer. The interface layer has a better lithium ion transmission efficiency, is not easy to shrink holes at low temperatures, can maintain the lithium ion transmission channel at low temperatures, and improve the low-temperature performance of lithium-ion batteries. However, the FS bond in Compound A has low bond energy and is easy to break, and then defluorinates with α-H on the carbonate compound, resulting in an increase in the acid value of the electrolyte. Therefore, Compound A is easy to produce acidic substances in the battery, which damages the SEI film and causes the battery's cycle performance to deteriorate. The compound B of the present application can not only polymerize at the negative electrode to form a high-toughness SEI, but also exhibits Lewis base characteristics, can complex the acidic substances produced by Compound A, and inhibit the damage of the acidic substances to the electrode electrolyte interface, and the battery's cycle performance is guaranteed. Therefore, the present invention utilizes the synergistic effect of compound A and compound B to reduce the interfacial side reactions of lithium-ion batteries during cycling and storage, effectively inhibit the decomposition of the SEI interface, and thus improve the cycling performance and low-temperature performance of lithium-ion batteries.
[0062] By comparing Example 8 with Examples 10 to 13, it can be seen that adding an auxiliary agent on the basis of the additive of the present invention can further improve the cycle performance and low-temperature discharge performance of the lithium-ion battery.
[0063] By comparing Examples 10 to 11 and Examples 14 to 16, it can be seen that when the VC / FEC mixed additive is used in the lithium-ion battery electrolyte, the cycle performance and low-temperature performance of the lithium-ion battery are greatly improved.
[0064] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention is described in detail with reference to the preferred embodiments, it is not limited to those listed in the embodiments. Those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A lithium ion battery electrolyte, characterized in that: It comprises a lithium salt, a non-aqueous organic solvent and an additive, wherein the non-aqueous organic solvent comprises a carbonate compound, and the additive comprises a compound A represented by structural formula I and a compound B represented by structural formula II; Wherein R1 is selected from halogen, R2 to R4 are each independently selected from halogen, alkyl, alkenyl, alkynyl or silane, m is selected from 0 or 1, and X is selected from carbon, sulfur or phosphorus.
2. The lithium ion battery electrolyte according to claim 1, characterized in that R2 to R4 are each independently selected from halogen, C1-C6 alkyl, C2-C6 alkenyl, C2-C6 alkynyl or C1-C6 silanyl, and R2 to R4 groups are the same.
3. The lithium ion battery electrolyte according to claim 1, characterized in that The compound A is selected from at least one of compounds A1 to A3:
4. The lithium ion battery electrolyte according to claim 1, characterized in that The compound B is selected from at least one of compounds B1 to B4:
5. The lithium ion battery electrolyte according to claim 1, characterized in that The mass percentage of the compound A in the lithium ion battery electrolyte is 0.1-10.0%; the mass percentage of the compound B in the lithium ion battery electrolyte is 0.1-10.0%.
6. The lithium ion battery electrolyte according to claim 1, characterized in that The lithium salt includes at least one of lithium hexafluorophosphate, lithium perchlorate, lithium tetrafluoroborate, lithium bis(fluorosulfonyl imide), lithium bis(trifluoromethylsulfonyl imide), lithium methane sulfonate, lithium trifluoromethyl sulfonate, lithium fluorosulfonate, lithium bis(oxalatoborate), lithium difluorooxalatoborate, lithium difluorophosphate, lithium difluorobis(oxalatophosphate), lithium diphosphate and lithium lower aliphatic carboxylate.
7. The lithium ion battery electrolyte according to claim 1, characterized in that: The non-aqueous organic solvent further comprises at least one of a carboxylate compound and an ether compound.
8. The lithium ion battery electrolyte according to claim 1, characterized in that It also includes an auxiliary agent, which is selected from vinylene carbonate, vinylene carbonate, fluoroethylene carbonate, vinyl sulfite, 1,3-propane sultone, 1,3-propylene sultone, 1,4-butane sultone, vinyl sulfate, succinic anhydride, maleic anhydride, 2-methylmaleic anhydride, methyl carbonate-2-propynyl ester, tetravinylsilane, triallyl isocyanurate, hexamethylene diisocyanate, o-phenanthroline, p-phenylene diisocyanate, 2, At least one of 4-toluene diisocyanate, N-phenylbis(trifluoromethanesulfonyl)imide, vinyl bissulfate, phenyl methanesulfonate, vinyl bissulfate, bis-spiro-propylene sulfate, hydroquinone difluorosulfonate, triallyl phosphate, tripropargyl phosphate, 2,4-butane sultone, isocyanoethyl methacrylate, methylene disulfonate, tris(trimethylsilyl)borate, tris(trimethylsilyl)phosphate, and tris(vinyldimethylsilyl)phosphate.
9. A lithium ion battery comprising a positive electrode and a negative electrode, characterized in that: It also includes the lithium ion battery electrolyte as claimed in any one of claims 1 to 8.
10. The lithium ion battery according to claim 9, characterized in that The active material of the positive electrode includes olivine-structured lithium-containing phosphate, lithium transition metal oxide and their respective modified compounds.
Citation Information
Patent Citations
Aqueous high-voltage electrolyte as well as preparation method and application thereof
CN111224171A
Non-aqueous electrolyte of lithium ion battery and lithium ion battery containing non-aqueous electrolyte
CN111934017A
Electrolyte for lithium ion battery, preparation method of electrolyte and lithium ion battery
CN113764736A
Electrolyte and lithium ion battery
CN115425293A
Secondary battery and electronic device
CN118763180A